2006
DOI: 10.1016/j.virol.2005.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Host cell killing by the West Nile Virus NS2B–NS3 proteolytic complex: NS3 alone is sufficient to recruit caspase-8-based apoptotic pathway

Abstract: The West Nile Virus (WNV) non-structural proteins 2B and 3 (NS2B-NS3) constitute the proteolytic complex that mediates the cleavage and processing of the viral polyprotein. NS3 recruits NS2B and NS5 proteins to direct protease and replication activities. In an effort to investigate the biology of the viral protease, we cloned cDNA encoding the NS2B-NS3 proteolytic complex from brain tissue of a WNV-infected dead crow, collected from the Lower Merion area (Merion strain). Expression of the NS2B-NS3 gene cassett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
70
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 39 publications
5
70
0
Order By: Relevance
“…Although further study is warranted, we speculate that different neurons may undergo cell-specific death programs in response to WNV infection. Flaviviruses can induce cell death directly through viral replication and the production of proapoptotic proteins (41,43,44,52,57). Notably, pancaspase and caspase 3 inhibitors reduced the WNV-mediated death of primary neurons, which is consistent with studies showing that caspase inhibitors reduced apoptosis after transgenic expression of the flavivirus NS3 and E genes (41,42,44).…”
Section: Vol 81 2007 Apoptosis Contributes To West Nile Virus Pathosupporting
confidence: 84%
See 1 more Smart Citation
“…Although further study is warranted, we speculate that different neurons may undergo cell-specific death programs in response to WNV infection. Flaviviruses can induce cell death directly through viral replication and the production of proapoptotic proteins (41,43,44,52,57). Notably, pancaspase and caspase 3 inhibitors reduced the WNV-mediated death of primary neurons, which is consistent with studies showing that caspase inhibitors reduced apoptosis after transgenic expression of the flavivirus NS3 and E genes (41,42,44).…”
Section: Vol 81 2007 Apoptosis Contributes To West Nile Virus Pathosupporting
confidence: 84%
“…Several WNV proteins may contribute directly to this process. Ectopic expression of the WNV NS3 protein or its helicase or protease domain induced apoptosis and activation of caspase 3 and 8 (44). Expression of WNV capsid protein either in vitro or in the striata of mouse brains also triggered apoptosis downstream of caspase 3 and caspase 9 activation (63).…”
mentioning
confidence: 99%
“…In addition, WNV infection initiates cellular apoptosis through a variety of caspase-dependent mechanisms, including induction of the unfolded protein response (UPR) (32), interaction of WNV proteins with apoptosis factors (42,57,58), and activation of inflammatory pathways (51). Cell death via these mechanisms contributes to the neuropathogenicity observed in WNV infection (44).…”
mentioning
confidence: 99%
“…In general, cytoplasmic RNA viruses such as flaviviruses are not believed to express their own miRNAs (although small RNAs derived from the viral genome can be identified in infected cells [38]). However, recent studies have demonstrated that viral infection can result in changes in expression of cellular miRNAs (9,24,33,42,45,55,58). Several reports have demonstrated that specific miRNAs can exert positive or negative influences on viral replica-tion through direct interaction with viral nucleic acid sequences (25,28,37,40), while other reports have demonstrated that individual miRNAs can affect viral replication via targeting cellular proteins (24,50).…”
mentioning
confidence: 99%
“…For example, WNV is known to induce Baxdependent or -independent apoptosis in cancer and brain cells (28). Factors such as NS2B-NS3 and capsid also enforce the cytotoxic effects of WNV through the apoptotic process (31). On the other hand, cellular components that protect host cells from WNV are not well known.…”
Section: Discussionmentioning
confidence: 99%